2011
DOI: 10.3109/10903127.2010.545480
|View full text |Cite
|
Sign up to set email alerts
|

Submersion and Early-Onset Acute Respiratory Distress Syndrome: A Case Report

Abstract: Drowning is a common cause of accidental death, particularly in younger people, and acute respiratory failure is common in these patients. This case report describes a healthy 18-year-old man who suffered a cardiorespiratory arrest due to submersion while swimming in a freshwater lake. First-responder cardiopulmonary resuscitation and defibrillation using an automated external defibrillator resulted in a return of spontaneous circulation. The patient was evacuated to a tertiary care center by a rotor-wing air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A study of 16 drowning cases, 4 of which died of dangerous underwater breath-holding behaviors (DUBBs), including intentional hyperventilation, static apnea, and hypoxic training [ 24 ]. Another study showed that a healthy 18-year-old male swimmer who suffered cardiopulmonary arrest while swimming in a freshwater lake is suspected to have died of secondary acute respiratory distress syndrome (ARDS) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 16 drowning cases, 4 of which died of dangerous underwater breath-holding behaviors (DUBBs), including intentional hyperventilation, static apnea, and hypoxic training [ 24 ]. Another study showed that a healthy 18-year-old male swimmer who suffered cardiopulmonary arrest while swimming in a freshwater lake is suspected to have died of secondary acute respiratory distress syndrome (ARDS) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory diseases are thought to be not completely reliable to the hypothesized swimming death mechanisms because few cases are supporting this mechanism. The included respiratory failure death cases are related to two concepts, DUBBs and ARDS [ 24 , 25 ]. Hyperventilation or breath-holding before diving or swimming reduces the body's storage of CO 2 and carbon dioxide partial pressure (PCO 2 ) to delay the brain's response to surface breathing which is an effective technique to trick their bodies into delaying the stimulation of breathing, thereby improving swimmers' performance.…”
Section: Discussionmentioning
confidence: 99%